Weaknesses of research methodologies on musculoskeletal disorders associated with mobile touch-screen devices - Elghomati, Ali; Mackieh, Adham; Babaqi, Tareq (Wiley, 2022)
The objective of the currently study is to point out the weaknesses of some recent researches, which were done about the effects or symptoms of using Touch Screen Mobile Devices on the human musculoskeletal system. In this article, we reviewed the research processes performed in recent 26 randomly selected papers about musculoskeletal disorder to clarify the common weaknesses of these published articles. The electronic database search and reference search were conducted in four different databases: Medline, PubMed, Web of Science, and Scopus. We noticed that none of the reviewed papers had performed the experimental design phase of a scientific research. Additionally they had not validated the assumptions of the statistical methods used in their researches. Therefore, their findings are doubtful. In this article, we proposed practical outlines for a reliable experimental research.
Keywords: experimental scientific research; musculoskeletal disorder; smartphones; statistical analysis; symptoms; tablets